AN ASSESSMENT OF PATIENT SATISFACTION IN DAY CARE SURGERY: A PROSPECTIVE OBSERVATIONAL STUDY - ANIL SHETTY; BLESSING DHAS A; Mishra, GOVINDRAJ BHAT M (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: This study aims to evaluate the patient’s satisfaction with anesthesia who underwent daycare surgery in terms of a “core questionnaire for the assessment of patient satisfaction for general daycare” (COPS-D) questionnaire. Methods: In this prospective observational study, we included 72 patients posted for day care surgery, belonging to ASA physical status 1 and 2. The patient’s demographic details, pre-operative assessment, anesthetic technique, and surgical consideration were all recorded, and informed consent was obtained from the respective participants in the pre-operative room. Once the post-anesthesia discharge scoring system criteria are fulfilled by the patient, a COPS-D questionnaire was obtained. Results: Results were analyzed according to the average score per question and average score per domain of the COPS-D questionnaire. It was found that the highest score was achieved by the question number (Q4) ‘‘How satisfied were you with the personal attention of the operation staff? which achieved an average score of 4.72±0.48 and the lowest score was achieved by (Q10) “How satisfied were you with the discharge procedure? which achieved an average score of 4.17±0.79. The overall satisfaction was 80%. Conclusion: The COPS-D questionnaire proved to be a useful tool in identifying points of patient satisfaction and these were correlated with patient variables such as age, sex, ASA physical status, anesthesia type, and surgical specialty with the ultimate goal of improving patient satisfaction in relation to anesthesia care.